Hubungan Pemberian Asi Eksklusif Dan Pola Mpasi Dengan Kejadian Stunting Pada Anak Usia 12-24 Bulan Di Pandeglang, Banten - Shakeela, Karenina (Publikasi Indonesia, 2022)
Background: Toddlers in the world are currently experiencing one of the most worrying nutritional problems, one of which is short toddlers or often said to be stunting. The aim is to determine the relationship between exclusive breastfeeding and complementary food patterns in children aged 12-24 months in Pandeglang, Banten to stunting cases. Methods: This type of research is quantitative research which requires an activity to collect data then processed and analyzed and then made a presentation of data based on the number or number done objectively. Results: It can be seen that the majority of respondents have toddlers with male gender as many as 35 people with a percentage of 51.5%. There are 4 babies who have low birth weight with a percentage of 5.9%. In the age group of maternal pregnancy, dominated by the age group 20-30 years as many as 40 people with a percentage of 58.8%. Conclusion: Based on the results of the study, the relationship between exclusive breastfeeding and complementary food patterns with the incidence of stunting in children aged 12-24 months in Pandeglang.